Estudo dos efeitos renais e mecanismos de morte celular induzidos pelo veneno da serpente Bothrops leucurus - Morais, Isabel Cristina Oliveira de (2011)
Bothrops venoms consist of complex mixture of active substances, mainly peptides and proteins, which interfere with many physiologic processes. Bothrops species are responsible for more than 20,000 accidents per year in Brazil—90% of all recorded snakebites. The Bothrops leucurus is an important venomous snake that inhabits the northeast of Brazil. The biological effects due envenomation have similar profile to that observed in other Bothrops, ie coagulant activity, hemorrhagic, fibrinolytic, and renal failure in vivo. The aim of this study was to investigate the effects of the Bothrops leucurus venom in the renal perfusion system and in cultured renal tubular cells of the type MDCK (Madin–Darby Canine kidney). Isolated kidneys from Wistar rats weighing 250 to 300g (n=5) were perfused with Krebs-Henseleit solution containing 6% of bovine serum albumin previously dialyzed for 120 minutes. The effects of Bothrops leucurus venom (VBl) (10μg/mL) were studied on the Perfusion Pressure (PP), Renal Vascular Resistance (RVR), Urinary Flow (UF), Glomerular Filtration Rate (GFR) Percentage of Sodium (%TNa+), Potassium (%TK+) and Chloride (%TCl-) Tubular Transport. B. leucurus venom (10 μg/mL) reduction the PP at 90 and 120 min and UF at 60 and 90 min. The glomerular filtration rate decreased at 60 and 90 min. The renal vascular resistance decreased at 120 min. It was also observed a decrease on percentual tubular transport of sodium (%TNa+) at 120 min and of chloride (%TCl-) at 60 and 90 min. MDCK cells were grown in plastic flasks at 37° C in a humidified atmosphere of 5% CO2 – air, with RPMI 1640 medium supplemented with 10% fetal calf serum. The treatment with VBl caused decrease in cell viability to the lowest concentration tested with an CI50 of 1.25 μg/mL. Flow cytometry with annexin V and propidium iodide showed that cell death occurred predominantly by necrosis. When apoptosis was analyzed by nuclear staining, it was observed significant increase in the percentage of cell death, VBl 2,5 μg/mL induced 6,8% apoptosis and VBl 1,25 μg/mL caused 5,8% of apoptosis after 24 h of treatment. VBl treatment (1,25 μg/mL) led to significant depolarization of the mitochondrial membrane potential. We found increased expression of genes involved in cell death by apoptosis in the lower concentrations tested. The ion Ca2+ signaling participates in cell death induced by the venom of B. leucurus. These results demonstrate that the venom of B. leucurus altered all the renal parameters assessed in isolated kidney perfusion and was cytotoxic to MDCK cell culture.